A study for the film cooling performance on the turbine blade suction side tip region under rotating conditions. (August 2019) - Wang, Haichao; Tao, Zhi; Zhou, Zhiyu; Zhou, Huimin; Ma, Yiwen; Li, Haiwang
Highlights: The leakage vortex after the double squealer tip attaches the wall well. For high blowing ratio one leg of counter rotating vortex pair is depressed. High density ratio promote film attachment but shorten the film trace length. Rotation strengthens the passage vortex and aggravates the film deflection. Abstract: The performance of the suction side tip region film cooling under rotating condition is investigated by numerical simulation methods in this paper. In the simulation, three classical types of tip structures, including flat tip, double squealer tip and single squealer tip, are chosen to investigate tip structure effects. The effects of blowing ratios, density ratios and rotating Reynolds numbers (Ro) are analyzed. The results showed that the film performance on the suction side tip region is mainly influenced by the tip leakage vortex and the passage vortex: the tip structure changes the flow field greatly. The leakage flow in the double squealer tip results attaches the suction side wall best. For high blowing ratio results one leg of the counter rotating vortex pair (CRVP) is compressed and swept off the wall. The other one is pushed onto the wall achieving the better film coverage. Similarly one leg of CRVP dominates the jet flow at the near hole exit region for low density coolant results. But for the downstream film cooling the low density coolant has better performance. Rotation changes the mainstream stricture. The passage vortex is strengthened as the Ro increases. So the film deflection becomes more and more obvious.